Tingkat Pengetahuan, Sikap dan Perilaku Mahasiswi Fakultas Kedokteran Universitas Sumatera Utara Tentang Kanker Serviks - Putri, Savira Laniari; Harahap, Feby Yanti (Faculty of Medicine, Universitas Andalas, 2022)
Cervical cancer is the fourth most common cancer among women worldwide. It can be prevented by HPV vaccination, pap smears examination, or avoidance of risk factors for cervical cancer. Objectives. To determined the level of knowledge, attitude and behavior about cervical cancer among students at the Faculty of Medicine, Universitas Sumatera Utara. Methods: This is a descriptive study with a cross-sectional design. Results: The highest percentage level of knowledge about cervical cancer and cervical cancer prevention was in a good category, 55 people (57.3%) and people (74%), respectively. In the category of attitudes towards cervical cancer prevention, the most common attitudes found were positive among as many as 96 people (100%). The behavior toward cervical cancer prevention, neutral behavior was the most common (82 people, 85.4%), followed by positive behavior (14 people, 14.6%) and negative behavior. Conclusion: Knowledge of cervical cancer is in a good category, knowledge of cervical cancer prevention is in a good category, and the attitude towards prevention of cervical cancer is in a positive category. The behavior toward cervical cancer prevention is in the neutral category.Keywords: Â attitudes, behavior, cervical cancer, prevention